A heuristic model linking yoga philosophy and self-reflection to examine underlying mechanisms of add-on yoga treatment in schizophrenia. (3rd May 2016) - Rao, Naren; Menon, Sangeetha
Abstract: Preliminary evidence suggests efficacy of yoga as add-on treatment for schizophrenia, but the underlying mechanism by which yoga improves the symptoms of schizophrenia is not completely understood. Yoga improves self-reflection in healthy individuals, and self-reflection abnormalities are typically seen in schizophrenia. However, whether yoga treatment improves impairments in self-reflection typically seen in patients with schizophrenia is not examined. This paper discusses the potential mechanism of yoga in the treatment of schizophrenia and proposes a testable hypothesis for further empirical studies. It is proposed that self-reflection abnormalities in schizophrenia improve with yoga and the neurobiological changes associated with this can be examined using empirical behavioural measures and neuroimaging measures such as magnetic resonance imaging.